Improving Students' Speaking Skills in an EFL Context - Naumoska Sarakinska, Biljana (International Balkan University, Skopje, 2016)
Learning a foreign language is acquiring, developing and improving a number of skills, and in this context learning English as a foreign language is no different. Among the skills that need to be mastered are reading, writing, listening and speaking. It goes without saying that one set of skills is not more important than another, however, it is safe to conclude that the ultimate aim of learning any foreign language is to facilitate communication. In this sense, we can say that speaking skills are often equated with communication skills, which, up to a certain extent, is true. Yet, it is important that we bear in mind the fact that communication is not solely identified with speaking, since communication can also include writing, listening, and up to a point, reading as well. Another important point that should be considered when discussing the acquisition, development and improvement of foreign language skills is that of instruction, learning, and feedback. The aim of this presentation is to provide some insight into how EFL students can improve their speaking skills in an EFL context, as well as the possibility of incorporating communicative grammar in practice, and the pedagogical implications in English language teaching.
Keywords: speaking skills, strategies, techniques, communication (skills)